Structural and functional characterisation of the collagen binding domain of fibronectin - Millard, CJ (2007)
Fibronectin is an extracellular multidomain glycoprotein that directs and regulates a variety of cell processes such as proliferation, development, haemostasis, embryogenesis, and wound healing. As a major component of blood, fibronectin exists as a soluble disulphide linked dimer, but it can also be incorporated into an insoluble cross-linked fibrillar network to form a major component of the extracellular matrix. Fibronectin is composed of an extended chain of module repeats termed Fn1, Fn2, and Fn3 that bind to a wide range of transmembrane receptors and extracellular matrix components, including collagen. The gelatin binding domain of fibronectin was first isolated as a 45kDa proteolytic fragment and has since been found to be composed of six modules: 6Fn1-1Fn2-2Fn2-7Fn1-8Fn1-9Fn1 (in this notation nFX represents the nth type X module in the native protein). This domain has been reported to bind to both collagen and denatured collagen (gelatin), but with 10-100 times higher affinity to the latter; it can be purified to homogeneity on a gelatin affinity column. In the work presented here, fragments of the gelatin binding domain are expressed in P. pastoris, purified to homogeneity, and investigated at the molecular level. Through a dissection approach, surface plasmon resonance (SPR) is used to characterise the recombinantly produced protein, to accumulate more information about the function of the full domain. NMR is used to assess the folding of the protein fragments at atomic resolution. In particular, the secondary structure of 8Fn1-9Fn1 is mapped using inter-strand NOEs, which suggests that the construct takes the fold of a pair of typical Fn1 modules. Gelatin affinity chromatography is used to confirm that both Fn1 and Fn2 modules contribute to gelatin binding, possibly in two clusters (1Fn2-2Fn2 and 8Fn1-9Fn1). The 7Fn1 module may perform a structural role in linking together these two interaction sites, in the same way as suggested for 6Fn1, which is thought to act in a structural manner to enhance the binding of 1Fn2-2Fn2 to gelatin. Three carbohydrate moieties are found on this domain, one on 2Fn2 and two on 8Fn1. Here, by means of expressing different protein length fragments, and by site directed mutagenesis, the role of each sugar chain is investigated independently. The sugar chain on 2Fn2 does not appear to promote binding to collagen, nor does the first sugar chain on 8Fn1 (N-linked to N497), implying another role for these sugars such as protection from proteolysis. However, the presence of at least a single GlcNAc sugar residue on the second sugar chain site on 8Fn1 (N- linked to N511) is essential for full affinity binding to collagen. Direct binding of the 8Fn1-9Fn1 module pair to collagen is assessed with a short collagen peptide and the binding is monitored by NMR. The peptide appears to bind, predominantly to the final strand of 8Fn1, the first β- strand of 9Fn1, and the linker between the two modules, with μM affinity. A model for bound peptide is proposed. The highly conserved amino acid motif Ile-Gly-Asp (IGD) is found on four of the nine N-terminal Fn1 modules of fibronectin. Tetrapeptides containing the IGD were demonstrated to promote the migration of fibroblast cells into a native collagen matrix. Two of these “bioactive” IGD motifs are found within the gelatin binding domain, one on 7Fn1 and one on 9Fn1. In this study, the motif in the 8Fn1-9Fn1 module pair is shown to be located in a tightly constrained loop within 9Fn1. By site directed mutagenesis, the IGD motifs of 7Fn1 and 9Fn1 are subjected to single amino acid substitutions, and their ability to stimulate cell migration assessed in our assay. By NMR, the fold of the IGD mutant proteins is found to be unaffected by the mutation with respect to the wild type, with the exception of small perturbations around the substitution site. While the wild type module is able to stimulate fibroblast migration, the mutant proteins show reduced or negligible bioactivity. The larger fragments show far more potency in stimulating fibroblast migration, with 8Fn1-9Fn1 (one IGD motif) 104 times more potent than the IGD peptide, and the full gelatin binding domain (two IGD motifs) 106 times more potent than the 8Fn1-9Fn1. Potential mechanisms for this enormous enhancement of the IGD potency in different contexts are discussed.